Convergence and impoverishment of fen communities in a eutrophicated agricultural landscape of the Czech Republic. Issue 2 (21st January 2017) - Navrátilová, Jana; Hájek, Michal; Navrátil, Josef; Hájková, Petra; Frazier, Ryan J.
Abstract: Questions: On‐going rapid loss of fen biodiversity in Central Europe is well known, but rigorous testing of this is complicated. We compared historical and present‐day vegetation plot records from a cultural landscape rich in fishponds, where recent eutrophication and water table manipulations threaten the unique fen diversity. We assess species composition change over the last 50 yr. Location: Třeboň Basin, Czech Republic. Methods: First, we revisited historical vegetation plots to collect present‐day data and then identified the most similar present‐day record (the present‐day counterpart ) because no permanent plots were available. Second, we inferred water level, pH and conductivity (a proxy of mineral richness) using a training set of present‐day field measurements, and calculated Ellenberg indicator values. Then we applied modified TWINSPAN classification, CCA, PERMANOVA, PERMDISP and RMANOVA in order to test changes in the species composition, β‐diversity and environmental conditions between the historical records and their present‐day counterparts . Results: Fen vegetation has persisted on half of the sites. Out of four vegetation types, poor fens and especially flooded fens were over‐represented in the present‐day subset, while rich fens and quaking fens were under‐represented. Overall species composition differed between historical plots and their present‐day counterparts, even within individual vegetation types. Historical rich fens showed significantly higher β‐diversity than their present‐day counterparts, which predominantly represent flooded fens. Inferred water level and its fluctuation, Ellenberg moisture and nutrient values have increased, while inferred pH, conductivity and Ellenberg light value have decreased. Conclusions: The historically wide array of fen vegetation has turned into a homogeneous and floristically depauperate set of acidic yet productive flooded fens with a high water level. Rich and quaking fens that were both low in nutrient availability and had a stable water level near the moss layer experienced a large and substantial reduction and have become rare in the landscape. Eutrophication combined with a lack of management has resulted in fen species persisting only in flooded fens. However, fluctuating water levels and high nutrient availability in flooded fens favour productive Sphagnum fens over the other vegetation types, and, importantly, do not support some endangered fen species. Abstract : The historically wide array of fen vegetation has turned into a homogeneous and floristically depauperate set of acidic yet productive flooded fens with a high water level. Fluctuating water levels and high nutrient availability favour productive Sphagnum fens over the other vegetation types, and importantly do not support some endangered fen species.